2001
DOI: 10.1002/mrd.1066
|View full text |Cite
|
Sign up to set email alerts
|

Specific localization of transcription factors in the chromatin of mouse mature spermatozoa

Abstract: We previously characterized a nuclease-hypersensitive fraction of mouse sperm chromatin, which is organized in a typical nucleosomal structure. A partial genomic library was constructed with the DNA from the nuclease-hypersensitive chromatin, which revealed a high content in retroposon/retroviral DNA sequences. Here we report that the cloned nuclease-hypersensitive DNA also contains clusters of potential sites for transcription factors: among those, binding sites for Oct-1, Oct-4, TBP, Ets-1, and C/EBP are mos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
23
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 43 publications
0
23
1
1
Order By: Relevance
“…For example, TBP was not detected in mature sperms by the immunochemical method (Martianov et al, 2002a and this study); however, an immunoprecipitation assay demonstrated that the TBP-binding sites in sperm appeared to be occupied. In addition, with the use of appropriate antibody and protocol, Oct-1, Oct-4, Ets-1, and C/EBP were detected in the sperm nucleus (Pittoggi et al, 2001). In the present study, some CFs, e.g., TFIIB, SRG3, and HDAC1 were not detected in the immunochemical assay but detected in Western blots.…”
Section: Discussioncontrasting
confidence: 51%
“…For example, TBP was not detected in mature sperms by the immunochemical method (Martianov et al, 2002a and this study); however, an immunoprecipitation assay demonstrated that the TBP-binding sites in sperm appeared to be occupied. In addition, with the use of appropriate antibody and protocol, Oct-1, Oct-4, Ets-1, and C/EBP were detected in the sperm nucleus (Pittoggi et al, 2001). In the present study, some CFs, e.g., TFIIB, SRG3, and HDAC1 were not detected in the immunochemical assay but detected in Western blots.…”
Section: Discussioncontrasting
confidence: 51%
“…The spermatozoon is a highly differentiated and transcriptionally silent cell; nevertheless, it does contain some transcription factors (Herrada & Wolgemuth 1997, D'Cruz et al 2001, Pittoggi et al 2001. Among them, Stat1 was reported in human spermatozoa, whereas Stat4 was reported in both human and mouse spermatozoa; mouse Stat4 was located in the sperm PT (Herrada & Wolgemuth 1997, D'Cruz et al 2001.…”
Section: Discussionmentioning
confidence: 99%
“…Even though the spermatozoon is considered as a transcriptionally silent cell, it does contain some transcription factors (Herrada & Wolgemuth 1997, D'Cruz et al 2001, Pittoggi et al 2001. In spermatozoa, the Jak-Stat members detected to date are tyrosine kinase 2 (Tyk2), Stat4 andStat1 (Herrada &Wolgemuth 1997, D'Cruz et al 2001).…”
Section: Introductionmentioning
confidence: 99%
“…The finding that ␤-arrestin2 mediates transactivation upon hOR17-4 stimulation suggests participation in nuclear functions in mammalian spermatozoa, despite the fact that these cells have a highly condensed, inactive chromatin structure. Interestingly, a growing number of studies indicate that the nucleus of mature spermatozoa contains potentially active chromatin domains (GardinerGarden et al, 1998;Pittoggi et al, 2001).…”
Section: Discussionmentioning
confidence: 99%